Planning of distribution networks in presence of Distributed Generators and cross-connections - Ziari, I.; Ledwich, G.; Ghosh, Arindam; Platt, G. (Institute of Electrical and Electronics Engineers, 2011)
In this paper, the optimal location and output power of Distributed Generators (DGs) along with the location and type of cross-connections are determined as the transformer and feeders are optimally upgraded. These are all to improve system reliability and to minimize line losses under load growth. Given this, an objective function is constituted, composed of the investment cost, loss cost, reliability cost, and the energy saving resulting from DG injection. As constraints, the bus voltage, line current, and DG power are maintained within their bounds. The modified discrete particle swarm optimization method is employed in this paper for optimizing this planning problem. The distribution system, connected to bus 4 of the Roy Billinton test system, is used to evaluate the proposed technique. Three different scenarios are assessed. In the first scenario, a basic planning approach is studied. In the second scenario, the use of DG is planned to avoid extra line and transformer upgrades. Finally, the proposed technique, in which all technologies are included, is investigated in the third scenario. The outcomes demonstrate that the lowest cost plan results when all technologies are incorporated as proposed in this work.